The Second Form At St Clare's - Blyton, Enid (London Darrell Waters Limited, 1973)
Part of the "Rewards" series covering a range of Enid Blyton's work from her stories for the very young, such as the adventures of "Brer Rabbit" and "Amelia Jane", to stories for older children including the "Malory Towers" books. This book follows the O'Sullivan twins at St Clare's school.